DEMOGRAPHIC DYNAMICS OF FINTECH ADOPTION: EXPLORING PATTERNS AND PREFERENCES IN AN EMERGING ECONOMY (IITM Journal of Business Studies, 2024)
In recent years, the global financial landscape  has undergone a significant transformation  propelled by the rapid proliferation of Financial  Technology (Fintech). This technological  revolution has not only reshaped traditional  financial services but has also democratized  access to financial products and services,  ushering in a new era of financial inclusion and  empowerment. Understanding the underlying  demographic dynamics behind Fintech  adoption has become increasingly crucial  for policymakers, financial institutions, and  market participants alike, especially within  emerging economies. This research aims to  delve into the intricate interplay between  demographic factors and Fintech adoption  within the context of emerging economies.  Through a multidimensional approach  encompassing quantitative analysis and  theoretical frameworks, the study endeavors  to investigate the patterns and preferences  across different demographic segments. By  analyzing data from 15 emerging countries  representing diverse regions across the globe,  the research seeks to uncover insights into  the drivers and barriers influencing Fintech  adoption.
Keywords: Fintech adoption; demographic factors; emerging economies; financial inclusion; technological innovation; multidimensional approach Top of Form